2012
DOI: 10.1063/1.4712092
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic properties of hollow glass microsphere/epoxy composites

Abstract: In this work, hollow glass microsphere (HGM) reinforced triglycidyl-p-aminophenol (TGPAP) epoxy composites was prepared and the influence of HGM on mechanical and thermal properties of the composites was investigated. Mechanical behaviors of the composites with various weight fractions of HGM from 0 to 9% were investigated in terms of impact property at both room temperature (RT) and liquid nitrogen temperature (77 K). The fracture surfaces of undoped epoxy and the composites were examined by scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The strong IR absorptions at 3341 and 1721 cm −1 corresponding to the stretching vibration of N–H and C=O, respectively, indicated that there exist carbamate groups of –NHCOO– in the prepared HT2P4 molecules [18,19,20]. Meanwhile, the strong absorption peaks at 3442 and 1111 cm −1 corresponding to the stretching vibration of –OH and C–O, respectively, showed the existence of the hydroxyl groups and ether bonds in the molecular structure of prepared HT2P4 [4]. Furthermore, HT2P4 showed a slight phase change behavior as shown in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong IR absorptions at 3341 and 1721 cm −1 corresponding to the stretching vibration of N–H and C=O, respectively, indicated that there exist carbamate groups of –NHCOO– in the prepared HT2P4 molecules [18,19,20]. Meanwhile, the strong absorption peaks at 3442 and 1111 cm −1 corresponding to the stretching vibration of –OH and C–O, respectively, showed the existence of the hydroxyl groups and ether bonds in the molecular structure of prepared HT2P4 [4]. Furthermore, HT2P4 showed a slight phase change behavior as shown in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
“…Their highly crosslinked microstructures endow them with many useful properties for industrial applications, for instance, high strength, excellent thermal stability, and good adhesion. Nevertheless, their resistance to crack initiation and propagation is poor due to their inherent brittleness, which affects their durability and strongly constrains their design parameters [1,2,3,4]. Thus, toughening epoxy resin has been a major research topic over the last three decades.…”
Section: Introductionmentioning
confidence: 99%
“…These syntactic foams are used as buoyancy aid materials for marine applications [17]. These closed pore structures impart increased specific strength, reduced density, reduced coefficient of moisture absorptions and prevents thermal and electrical transports [18][19][20][21][22]. Syntactic foam properties are tailorable to good range and can be casted to any intricate shapes.…”
Section: Reinforcement Materials In Polymer Compositesmentioning
confidence: 99%